Changes in SIRT gene expression during odontoblastic differentiation of human dental pulp cells - Young-Eun Jang; Su-Hee Go; Bin-Na Lee; Hoon-Sang Chang; In-Nam Hwang; Won-Mann Oh; Yun-Chan Hwang (Korean Academy of Conservative Dentistry, 2015)
Objectives The aim of this study was to investigate the expression of 7 different sirtuin genes (SIRT1-SIRT7) in human dental pulp cells (HDPCs), and to determine the role of SIRTs in the odontoblastic differentiation potential of HDPCs. Materials and Methods HDPCs were isolated from freshly extracted third molar teeth of healthy patients and cultulred in odontoblastic differentiation inducing media. Osteocalcin (OCN) and dentin sialophosphoprotein (DSPP) expression was analyzed to evaluate the odontoblastic differentiation of HDPCs by reverse transcription-polymerase chain reaction (RT-PCR), while alizarin red staining was used for the mineralization assay. To investigate the expression of SIRTs during odontoblastic differentiation of HDPCs, real time PCR was also performed with RT-PCR. Results During the culture of HDPCs in the differentiation inducing media, OCN, and DSPP mRNA expressions were increased. Mineralized nodule formation was also increased in the 14 days culture. All seven SIRT genes were expressed during the odontogenic induction period. SIRT4 expression was increased in a time-dependent manner. Conclusions Our study identified the expression of seven different SIRT genes in HDPCs, and revealed that SIRT4 could exert an influence on the odontoblast differentiation process. Further studies are needed to determine the effects of other SIRTs on the odontogenic potential of HDPCs.